Advancing the development and application of decision support systems for sustainable brownfield redevelopment. - Hammond, Ellis Bernard (Cranfield University, 2023)
The redevelopment of brownfield sites is a vital part of ensuring sustainable urban development but has a range of challenges, including contamination and/or geotechnical hazards, leading to risk and cost implications. Brownfield redevelopment involves multiple stakeholders, from land use planners, land developers, and specialist consultants, to local community groups, and neighbouring residents. Understanding complex data and information can be difficult for decision-makers, which is exacerbated when communicating development scenarios and options with others. To support stakeholders, digital tools are often used, including specialised Decision Support Systems (DSSs). This PhD research investigates and contributes to the advancement of brownfield redevelopment DSSs. Existing and emerging challenges are evaluated, identifying improvement opportunities through a critical review of literature and large-scale sector- wide stakeholder consultation. A novel WebGIS-based DSS was developed in collaboration with land use planning stakeholders, applying the DSS to an area of post- industrial land within the Liverpool city region, UK. The DSS was evaluated through user testing, where improvements were identified and implemented, and verified, using a combination of empirical and user-testing methods. Overall, the approach and application of this PhD research demonstrates modern user led DSS development for brownfield applications, overcoming many of the limitations of existing work. The use of the DSS to support early-stage planning and redevelopment of brownfield land is aligned with and informs, multiple current policies for sustainable development and the use of applied digital technologies in planning and land development.
Keywords: sustainable urban development; digital tools; GIS; land use planning; stakeholder engagement; decision support tool